2009
DOI: 10.1101/gad.479209
|View full text |Cite
|
Sign up to set email alerts
|

A phosphorylation-acetylation switch regulates STAT1 signaling

Abstract: Cytokines such as interferons (IFNs) activate signal transducers and activators of transcription (STATs) via phosphorylation. Histone deacetylases (HDACs) and the histone acetyltransferase (HAT) CBP dynamically regulate STAT1 acetylation. Here we show that acetylation of STAT1 counteracts IFN-induced STAT1 phosphorylation, nuclear translocation, DNA binding, and target gene expression. Biochemical and genetic experiments altering the HAT/HDAC activity ratio and STAT1 mutants reveal that a phospho-acetyl switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
239
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(256 citation statements)
references
References 51 publications
13
239
4
Order By: Relevance
“…This event could be counteracted by dephosphorylation or CBP acetylation, which promotes STAT1 nuclear export (Kra¨mer et al, 2006). Once acetylated, STAT1 can be deacetylated by HDAC3, as well as HDAC1 and 2, thus permitting its phosphorylation and reactivation (Klampfer et al, 2004;Kra¨mer et al, 2009). Although HDACs promote STAT1 activation and nuclear import, their effects on STAT3 is exactly the opposite (Figure 1).…”
Section: Hdacs In the Stat And Nf-kb Pathwaysmentioning
confidence: 99%
“…This event could be counteracted by dephosphorylation or CBP acetylation, which promotes STAT1 nuclear export (Kra¨mer et al, 2006). Once acetylated, STAT1 can be deacetylated by HDAC3, as well as HDAC1 and 2, thus permitting its phosphorylation and reactivation (Klampfer et al, 2004;Kra¨mer et al, 2009). Although HDACs promote STAT1 activation and nuclear import, their effects on STAT3 is exactly the opposite (Figure 1).…”
Section: Hdacs In the Stat And Nf-kb Pathwaysmentioning
confidence: 99%
“…STAT1 knock-out mice show high susceptibility to microbial and viral infections and tumor formation due to the abrogation of the induction of several well known IFN-inducible genes (12,13). As an essential molecule in IFN signaling, STAT1 has been reported to be controlled by post-translational modifications including phosphorylation, acetylation, and ubiquitination (14,15).…”
mentioning
confidence: 99%
“…We favor the former hypothesis because of the close proximity of the Tyr-701 and Ser-708 residues, as phosphorylation at Tyr-701 may result in steric hindrance of Ser-708 phosphorylation. Importantly, we note that Tyr-701 phosphorylation has been shown to diminish at later time points after IFN stimulation or virus infection because of nuclear STAT1 acetylation and dephosphorylation of Tyr-701 by tyrosine phosphatase TCP45, which has been reported previously (40,58,59). Additionally, chromatin-bound STAT1 can be phosphorylated at Ser-727, resulting in its sumoylation by UBC9 (60,61).…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, chromatin-bound STAT1 can be phosphorylated at Ser-727, resulting in its sumoylation by UBC9 (60,61). As unphosphorylated STAT1 cycles back to the cytoplasm via CRM1-mediated nuclear export, acetylation and sumoylation results in STAT1 latency by inhibiting IFN-induced STAT1 Tyr-701 phosphorylation, which should then permit Ser-708 phosphorylation (58,59,61). These studies concluded that non-tyrosine phosphorylated STAT1 is the "unphosphorylated STAT1," which functions to sustain expression of some ISGs (62,63).…”
Section: Discussionmentioning
confidence: 99%